2022
DOI: 10.3389/ti.2022.10489
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplant Recipient Characteristics Associated With Worse Post-Transplant Outcomes in Using Elderly Donors

Abstract: Advanced age of liver donor is a risk factor for graft loss after transplant. We sought to identify recipient characteristics associated with negative post-liver transplant (LT) outcomes in the context of elderly donors. Using 2014–2019 OPTN/UNOS data, LT recipients were classified by donor age: ≥70, 40–69, and <40 years. Recipient risk factors for one-year graft loss were identified and created a risk stratification system and validated it using 2020 OPTN/UNOS data set. At transplant, significant recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Recipients in the LDLT ≥70y group had significantly lower rates of HCC diagnosis with and without cirrhosis versus the DDLT ≥70y group (Table 2). Similarly, significantly less disease burden was found in the LDLT ≥70y group when compared to recipients in the DDLT ≥70y group in terms of lower MELD score (15 (11-21) vs. 17 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)…”
Section: Recipient Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recipients in the LDLT ≥70y group had significantly lower rates of HCC diagnosis with and without cirrhosis versus the DDLT ≥70y group (Table 2). Similarly, significantly less disease burden was found in the LDLT ≥70y group when compared to recipients in the DDLT ≥70y group in terms of lower MELD score (15 (11-21) vs. 17 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)…”
Section: Recipient Characteristicsmentioning
confidence: 90%
“…The important role of donor age on post-transplant outcomes has been vastly studied, primarily for DDLT. 20,21 However, evidence regarding the impact of donor age in LDLT recipient outcomes is scarce and contradictory. To date, there is no current cutoff for upper donor age in LDLT, and practices vary among centers.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the impact of elderly liver grafts on post-transplant mortality, a phenomenon that exhibits variability in the age of recipients, particularly among younger recipients [9,26,27]. LT from donors aged 60 or older has great transplant outcomes, with no significant difference in 1-year and 5-year survival rates compared with patients receiving old and normal liver grafts [28][29][30].…”
Section: Patient and Graft Survivalmentioning
confidence: 99%
“…Preferred recipients who are less likely to incur additional risks associated with aged donor liver include the following: (1) first-time transplant recipients over the age of 45 years, (2) a body mass index (BMI) < 35, and (3) a cold ischemic time < 8 h [140]. Other recipient factors, such as mechanical ventilation, portal thrombus, and low serum sodium value, appear to also be important in the survival of aged grafts [141]. Interestingly, the age of recipients may not be a major risk factor [141][142][143].…”
Section: Controversy About Age Factor In Liver Surgery Of the Elderlymentioning
confidence: 99%
“…Other recipient factors, such as mechanical ventilation, portal thrombus, and low serum sodium value, appear to also be important in the survival of aged grafts [141]. Interestingly, the age of recipients may not be a major risk factor [141][142][143].…”
Section: Controversy About Age Factor In Liver Surgery Of the Elderlymentioning
confidence: 99%